An ultrathin suspended hydrophobic porous membrane for high-efficiency water desalination. (December 2017) - Perrotta, M.L.; Saielli, G.; Casella, G.; Macedonio, F.; Giorno, L.; Drioli, E.; Gugliuzza, A.
Graphical abstract: Highlights: Ultrathin fluorinated porous membrane for thermally efficient water desalination. Fine structure-transport relations for unusual productivity-efficiency trade-off. Novel nanostructured membrane for new-concept fruitful water desalination. Abstract: An ultrathin highly fluorinated porous membrane was designed for a large production of desalted water at very low energy consumption. Imprinting water droplets were used through a low thermally conductive tetra-fluoroethylene (TFE)/2, 2, 4-trifluoro-5-tri-fluorometoxy-1, 3-dioxol (TIT) (HYFLON AD 60) solution and the generated porous nanofilm was suspended onto a polyethersulfone (PES) honeycomb texture. The very tiny fluorinated thickness together with a large number of small-shaped pores provided the membrane for enhanced anti-wetting surface properties, extremely reduced resistance to water vapor transfer and outstanding thermal efficiency. Fine materials structure-transport relations let the membrane reach unusual productivity-efficiency trade-off during water desalination via thermally driven membrane distillation. The exceptional performance affords this novel nanostructured membrane to catalyze the accomplishment of new-concept water desalination processes.